Zero reduction codes for efficient transmission and enhanced brightness in visible light communication - Kim, Kyuntak; Lee, Kyujin; Lee, Kyesan (IET optoelectronics, 2017)
In this study, the authors propose novel zero reduction codes to simultaneously provide effective illumination and communication services in visible light communications (VLC). In general, the brightness of light-emitting diode illuminations can be enhanced by increasing the duty cycle ratio (DCR) but in such cases, the bit error rate (BER) performance is significantly degraded in the VLC systems. This is because the decision interference of received 0 and 1 bits is increased owing to the decision boundary overlapped. The proposed coding scheme can improve the brightness without increasing DCR and also achieve the enhanced BER performance compared to the conventional modulation schemes such as variable pulse-position modulation or variable on–off keying. The simulations results demonstrate that the proposed coding scheme provides the superior brightness and BER performances.